Logical Reasoning - Dowden, Bradley H. (Open textbook library., 2017)
The goal of this book is to improve your logical-reasoning skills. These skills are also called "critical thinking skills." They are a complex weave of abilities that help you get someone's point, generate reasons for your own point, evaluate the reasons given by others, decide what or what not to do, decide what information to accept or reject, explain a complicated idea, apply conscious quality control as you think, and resist propaganda. Your most important critical thinking skill is your skill at making judgments─not snap judgments that occur in the blink of an eye, but those that require careful reasoning. This book is also available as an adaptable Word file.